1957
DOI: 10.1039/jr9570001592
|View full text |Cite
|
Sign up to set email alerts
|

306. Actinomycin. Part III. The reaction of actinomycin with alkali

Abstract: The production and purification of actinomycin B are described. Addition of dilute alkali to an alcoholic solution of actinomycin causes a marked hypsochromic effect which is reversible. The reaction obeys secondorder kinetics and is interpreted as a fission of the oxygen bridge of the phenoxazin-3-one nucleus, giving rise to a highly strained and non-planar quinone anil. The reverse reaction involves two stages ; ring closure and elimination of water. Isatin, another molecule which shows a hypsochromic shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

1958
1958
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…3H-phenoxazine 1. Many molecules with antiviral, antibiotic and anticarcinogenic effects have a phenoxazine ring in common [1][2][3]. It has been shown that the tricyclic ring system intercalates between adjacent G-C base pairs inhibiting transcription of RNA polymerase.…”
Section: Introductionmentioning
confidence: 99%
“…3H-phenoxazine 1. Many molecules with antiviral, antibiotic and anticarcinogenic effects have a phenoxazine ring in common [1][2][3]. It has been shown that the tricyclic ring system intercalates between adjacent G-C base pairs inhibiting transcription of RNA polymerase.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 10a, which participates in the structure of the actinomycins was prepared according to ANGYAL et a1. 14). The preparation of 10b is described in Scheme 2, the free hydroxylamine 8 underwent rearrangement with TsCI/NEt3 to give the crystalline tosylate 9 in good yield, from which the aminophenol 10b was easily obtained by sodium naphthalene cleavage in 5a, b, in addition to the parent peak M+ which was always present, the main fragmentations of A2318711)…”
Section: Introduction Ofmentioning
confidence: 99%
“…We first examined whether a triflate compound would be a suitable partner in a Stille cross-coupling reaction. Adapting methods used for the preparation of the parent heterocyclic system, 6 was easily produced by reaction of 5 with 1,1‘-carbonyldiimidazole (CDI) in refluxing THF solution and was then reacted with Tf 2 O in dichloromethane at low temperature (Scheme ) . We found that 7 was produced in the reaction with Tf 2 O but was prone to reversion to 6 during purification, and thus we were unable to isolate it.…”
mentioning
confidence: 99%